2022
DOI: 10.3390/molecules27165310
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Antimicrobial Activities of Silver Nanoparticles Using Calotropis gigantea from Ie Seu-Um Geothermal Area, Aceh Province, Indonesia

Abstract: Herein, we report our success synthesizing silver nanoparticles (AgNPs) using aqueous extracts from the leaves and flowers of Calotropis gigantea growing in the geothermal manifestation Ie Seu-Um, Aceh Besar, Indonesia. C. gigantea aqueous extract can be used as a bio-reductant for Ag+→Ag0 conversion, obtained by 48h incubation of Ag+, and the extract mixture in a dark condition. UV–Vis characterization showed that the surface plasmon resonance (SPR) peaks of AgNPs-leaf C. gigantea (AgNPs-LCg) and AgNPs-flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 53 publications
4
28
1
Order By: Relevance
“…The Ag-NPs formation was visually indicated by the development of a dark reddish-brown color in the reduction mixture. In the same way, previous reports have shown that the color changes from green to yellow-brown [29][30][31] or dark brown [32][33][34] after the green synthesis of Ag-NPs. The ability of F. sycomorus leaf extract to reduce Ag + ions to Ag-NPs in the current study is in line with other studies that reported Ag-, Au-, and Cu-NPs formation through F. sycomorus extracts [35][36][37].…”
Section: Green Synthesis Of Ag-nps Through Ficus Sycomorus Leaf Extractsupporting
confidence: 71%
“…The Ag-NPs formation was visually indicated by the development of a dark reddish-brown color in the reduction mixture. In the same way, previous reports have shown that the color changes from green to yellow-brown [29][30][31] or dark brown [32][33][34] after the green synthesis of Ag-NPs. The ability of F. sycomorus leaf extract to reduce Ag + ions to Ag-NPs in the current study is in line with other studies that reported Ag-, Au-, and Cu-NPs formation through F. sycomorus extracts [35][36][37].…”
Section: Green Synthesis Of Ag-nps Through Ficus Sycomorus Leaf Extractsupporting
confidence: 71%
“…The key point in the successful synthesis of nanoparticles, however, is the availability of functional groups in bioreductants such as carboxylic, hydroxyl, and carbonyl groups that are reported to be involved in the bioreduction of Ag ions to NP along with stabilizing properties [20,21]. A variety of studies have been performed in recent years aimed at the synthesis of AgNPs using a diverse range of plant materials such as Calotropis gigantea [22], Annona Squamosa [23], Acer oblongifolium [24], Cascabela thevetia [25], Cymbopogon citratus [26], Eucalyptus globulus, and Salvia officinalis [27]. However, due to the relative diversity and stability of secondary metabolites, green tea leaves are most frequently reported in the literature as a natural source of reducing agents used in the biosynthesis of AgNPs [13,28].…”
Section: Introductionmentioning
confidence: 99%
“…The steroid and terpenoid test was conducted using the Liberman-Burchard reagent, whereas for the alkaloid test, we used Mayer, Dragendorff and Wagner reagents. The phenolic test used FeCl 3 , the flavonoid test used Mg powder and the tannin test used gelatin and sulfuric acid [ 52 ].…”
Section: Methodsmentioning
confidence: 99%